The effects of saccharin on the electrodeposition of NiCoFe films on a flexible substrate. (20th August 2021) - Budi, Setia; Manaf, Azwar
Abstract: In this work, the influence of saccharin on the electrodeposition of NiCoFe film on a flexible substrate was investigated. NiCoFe electrodeposition was carried out at different potentials from electrolytes both with and without saccharin. The addition of saccharin modified the nuclei growth mechanism, making the growth phase slower than that in the saccharin-free electrolyte. Ohm's law suggested that the two electrolytes differed in their resistance values. The presence of saccharin increased the current efficiency of NiCoFe electrodeposition at all co-deposition potentials and slightly enhanced the deposition rate due to the inhibition of hydrogen evolution during the reaction. The addition of saccharin also significantly decreased the anomalous co-deposition of NiCoFe compared to that which took place in the saccharin-free system. This approach successfully grew the crystalline phase of NiCoFe films on indium tin oxide-coated flexible polyethylene terephthalate substrate by varying the applied co-deposition potential, which controlled the chemical composition of the films.